Fairness ex ante & ex post: The benefits of renegotiation in media markets - Christoph Engel; Michael Kurschilgen (Max Planck Institute for Research on Collective Goods, 2010)
The market for copyrights is characterised by a highly skewed distribution of profits: very few movies, books and songs generate huge profits, whereas the great bulk barely manages to recover production cost. At the moment when the owner of intellectual property grants a licence ('ex ante'), neither party knows the true value of the traded commodity. A seemingly odd norm from German copyright law, the so-called bestseller provision, stipulates that the seller of a licence has a legally enforceable right to a bonus in case the work ('ex post') turns out a blockbuster. We experimentally explore the effect of the provision on market prices, on the number of deals struck and on perceived fairness. Our results show that the provision leads to lower prices for copyrights. More copyrights trade. The buyers perceive less ex-post unfairness.
Keywords: C91; D03; K12; 330; experiment; fairness; Copyright; Uncertainty; Urheberrecht; Medienökonomik; Preis; Risiko; Lizenzvergabe; Provision; Gerechtigkeit; Test; Deutschland